Integrated Development of Rural Energy Systems through Pocket Area Approach for Energy Services: The REDP Experience, Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Micro-hydro technologies together with other renewable energy technologies are being disseminated in various parts of Nepal to provide basic energy services as per the demand of the individual household or a particular community. These technologies use an integrated approach that helps address rural energy needs by providing basic rural energy services. The planning and implementation of rural energy systems in an integrated manner through the ‘Pocket Area Approach’, which takes into account the entire geographical area for the intervention, has been experimented in some of the pockets area in the country and is found quite effective to cater to basic rural energy services to the entire population of the area. This paper illustrates the approach and results achieved by Rural Energy Development Program (REDP).DOI: http://dx.doi.org/10.3126/hn.v9i0.7072 Hydro Nepal Vol.9 July 2011 44-47